Comparison of Biometric Information During Learning of Visual- and Text-Based Programming Languages - Umezawa, Katsuyuki; Nakazawa, Makoto; Hirasawa, Shigeichi (2023 8th International STEM Education Conference (iSTEM-Ed), 2023)
Novice programmers often start with visual-based programming languages, such as Blockly or Scratch, whereas experts tend to use text-based programming languages, such as C, C++, Java, or Python. However, a seamless transition from a visual- to a text-based language is yet to be established. Our study proposes an approach for this transition by introducing intermediate content with features that bridge the gap between visual- and text-based languages, as demonstrated in our previous study. We also show that incorporating this intermediate content enhances understanding of the text-based language. In this study, we measure learners' biometric information during their course of learning of both visual- and text-based languages, aiming to identify any differences in the biometric information during the training process.